2015
DOI: 10.1134/s0036023615050095
|View full text |Cite
|
Sign up to set email alerts
|

Internal mobility, phase transitions, and ionic conductivity in (NH4)6KZr4F23 and (NH4)6KHf4F23

Abstract: The ion mobility, phase transitions (PTs), and conductivity in (NH 4 ) 6 KZr 4 F 23 (I) and (NH 4 ) 6 KHf 4 F 23 (II) have been studied by 1 H and 19 F NMR, DSC, and impedance spectroscopy. Types of ion motion in the fluorides and ammonium sublattices have been determined in the temperature range 150-480 K, and their activation energies have been evaluated. Compounds I and II undergo phase transitions in the temperature ranges 400-440 and 419-440 K, respectively, to form high temperature modifications. The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Due to similarity of the IR spectra of the compounds in addition to the XRD data and taking into account the structure of the (NH 4 ) 6 LiZr 4 F 23 , it was suggested that compounds (NH 4 ) 6 LiZr 4-n Hf n F 23 have a chain structure which is analogous to the structure of (NH 4 ) 6 LiZr 4 F 23 . Taking into account the presence of phase transitions in the compounds (NH 4 ) 6 MZr(Hf) 4 F 23 (M = Li, Na, K, Rb) [11][12][13][14], it is quite ordinary that it will be attributed to (NH 4 ) 6 LiZr 4-n Hf n F 23 . This suggestion was confirmed by DSC data.…”
Section: Resultsmentioning
confidence: 99%
“…Due to similarity of the IR spectra of the compounds in addition to the XRD data and taking into account the structure of the (NH 4 ) 6 LiZr 4 F 23 , it was suggested that compounds (NH 4 ) 6 LiZr 4-n Hf n F 23 have a chain structure which is analogous to the structure of (NH 4 ) 6 LiZr 4 F 23 . Taking into account the presence of phase transitions in the compounds (NH 4 ) 6 MZr(Hf) 4 F 23 (M = Li, Na, K, Rb) [11][12][13][14], it is quite ordinary that it will be attributed to (NH 4 ) 6 LiZr 4-n Hf n F 23 . This suggestion was confirmed by DSC data.…”
Section: Resultsmentioning
confidence: 99%